Descriptions and synonymies in American Desmiphorini (Coleoptera, Cerambycidae, Lamiinae) - Santos-Silva, Antonio; Wappes, James E.; Galileo, Maria Helena M. (Zootaxa, 2018)
Estoloides (Parestoloides) Breuning, 1940, and Mimestoloides Breuning, 1974 are synonymized with Estoloides Breuning, 1940. Mimestoloides Breuning, 1980 is synonymized with Spinestoloides Breuning, 1954. Estoloides aurantius Martins & Galileo, 2010 is synonymized with E. scabracaulis Chemsak & Noguera, 1993. Estoloides modica Chemsak & Noguera, 1993 is synonymized with E. chamelae Chemsak & Noguera, 1993. Estoloides (Spinestoloides) spinipennis Breuning, 1974, is synonymized with Esthlogena monticola (Fisher, 1942). Estoloides (Spinestoloides) Breuning, 1954 is considered a genus different from Estoloides. Notes on Pseudestoloides Breuning and Heyrovsky, 1961, Pseudestoloides costaricensis Breuning and Heyrovsky, 1961, Pseudestoloides affinis Martins and Galileo, 2009, and on the type of Estoloides (Parestoloides) costaricensis Breuning, 1940, are provided. Pseudestoloides hiekei Breuning, 1974, is transferred to Estoloides. The following new combinations are established: Spinestoloides monticola; Spinestoloides fasciatus (Martins & Galileo, 2010); Spinestoloides benardi (Breuning, 1980); Estoloides andresi (Breuning, 1974); and Estoloides hiekei (Breuning, 1974). With the synonymy of Estoloides (Parestoloides), the following species have the subgenus removed from their names: Estoloides basigranulata Breuning, 1943: E. costaricensis Breuning, 1940; E. esthlogenoides Breuning, 1943; and E. parva Breuning, 1940. The following new species are described: Estoloides vandenberghei, from Nicaragua; E. maesi, from Nicaragua; E. nayeliae, from Mexico; E. noguerai, from Mexico and Nicaragua; E. chiapensis, from Mexico; E. pubescens, from Mexico; E. schusteri, from Guatemala; E. dthomasi, from Mexico; E. morrisi, from Mexico; E. giesberti, from Honduras; E. uyucana, from Honduras; Spinestoloides hefferni from Panama; and Pseudestoloides bingkirki from Nicaragua. The male of Spinestoloides spinipennis (Breuning, 1954), and the female of Estoloides prolongata are described for the first time. Keys to separate Estoloides, Pseudestoloides and Spinestoloides, from each other, and to species of Pseudestoloides and Spinestoloides are provided. Estoloides chamelae is newly recorded from Chiapas, Colima, Oaxaca and Guerrero in Mexico; E. prolongata is newly recorded from Costa Rica; and E. rufipes is newly recorded from the Brazilian state of Espírito Santo. The holotypes of Estoloides alboscutellaris Breuning, 1943 (Fig. 13), E. annulicornis Breuning, 1940 (Fig. 14), and E. reflexa Breuning, 1940 (Fig. 15) are also figured for the first time.